2006
DOI: 10.1136/oem.2005.022418
|View full text |Cite
|
Sign up to set email alerts
|

Occupational trichloroethylene exposure and non-Hodgkin’s lymphoma: a meta-analysis and review

Abstract: Methods: Meta-analysis and review of 14 occupational cohort and four case-control studies of workers exposed to trichloroethylene (TCE) to investigate the relation between TCE exposure and the risk of nonHodgkin's lymphoma (NHL). Studies were selected and categorised based on a priori criteria, and results from random effects meta-analyses are presented. Results: The summary relative risk estimates (SRRE) for the group of cohort studies that had more detailed information on TCE exposure was 1.29 (95% CI 1.00 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 78 publications
3
29
0
Order By: Relevance
“…Based on our data, we observed an increase in risk of PTCL and, specifically, ALCL, for textile workers. Exposures related to textile work include: dust, endotoxin (a bacterial contaminant of raw cotton fiber and cotton dust), assorted dyes, and chemicals such as trichloroethylene, which has previously been linked to lymphoma risk (33)(34)(35)(36)(37)(38). We also report that electrical fitters had increased odds of developing ALCL and angioimmunoblastic lymphoma.…”
Section: Discussionmentioning
confidence: 52%
“…Based on our data, we observed an increase in risk of PTCL and, specifically, ALCL, for textile workers. Exposures related to textile work include: dust, endotoxin (a bacterial contaminant of raw cotton fiber and cotton dust), assorted dyes, and chemicals such as trichloroethylene, which has previously been linked to lymphoma risk (33)(34)(35)(36)(37)(38). We also report that electrical fitters had increased odds of developing ALCL and angioimmunoblastic lymphoma.…”
Section: Discussionmentioning
confidence: 52%
“…13 Virtually every subsequent comprehensive review and meta-analysis of well-conducted occupational cohort studies over the last two decades, with one exception, 14 has generally found no convincing evidence to support a causal association between occupational exposure to TCE and cancer. [15][16][17][18][19][20][21][22] Results suggestive of an association between TCE exposure and cancer have derived almost exclusively from recently conducted community-based casecontrol studies. [23][24][25] Employment histories in community studies are self-reported and are quite diverse and heterogeneous in terms of jobs, industry, and geographic location.…”
Section: Discussionmentioning
confidence: 98%
“…Concerns remain, however, about the possible human carcinogenicity of TCE arising from presumably very high chronic TCE exposures that have occurred in the past in a few occupational settings, 21 but to date there is no convincing evidence from well-conducted cohort studies of workers known to be exposed to TCE that such exposure is associated with cancer risk. [15][16][17][18][19][20]22 Perchloroethylene, also known as tetrachloroethylene, has been used as an industrial solvent for more than 60 years. In 1995, the IARC concluded that there is limited evidence in humans for the carcinogenicity of PCE, 13 based primarily on epidemiologic reports of increased risks of cancer of the esophagus, bladder, cervix, and NHL among dry cleaning workers.…”
Section: Discussionmentioning
confidence: 99%
“…The carcinogenicity of TCE, particularly exposures incurred in occupational settings, has been reviewed in several publications (Weiss 1996;Alexander et al 2006;Mandel et al 2006;Chiu et al 2006;Scott and Chiu 2006;Mandel 2001; International Agency for Research on Cancer 1995;Chen and Seaton 1996;Harth et al 2005;McLaughlin and Blot 1997;Lynge et al 1997;Mandel and Kelsh 2001;Lavin et al 2000;Wartenberg et al 2000;Wong 2004). Wartenberg et al (2000) evaluated over 20 cancer sites, including liver, in their quantitative summary of epidemiologic studies of TCE.…”
Section: Introductionmentioning
confidence: 98%
“…Benzene and other petroleumbased products, for instance, were common ingredients in degreasers, and solvents such as mineral spirits, have been used in cleaning machinery [National Institute for Occupational Safety and Health (NIOSH) 1977]. Thus, interpretation of findings can be limited because few studies have analytically isolated occupational TCE exposure, and most studies have relied upon job title or occupational group as a surrogate for exposure (Wartenberg et al 2000;Mandel et al 2006).…”
Section: Introductionmentioning
confidence: 99%